2018
DOI: 10.1038/s41419-018-0631-9
|View full text |Cite
|
Sign up to set email alerts
|

FOXM1 contributes to taxane resistance by regulating UHRF1-controlled cancer cell stemness

Abstract: Therapy-induced expansion of cancer stem cells (CSCs) has been identified as one of the most critical factors contributing to therapeutic resistance, but the mechanisms of this adaptation are not fully understood. UHRF1 is a key epigenetic regulator responsible for therapeutic resistance, and controls the self-renewal of stem cells. In the present study, taxane-resistant cancer cells were established and stem-like cancer cells were expanded. UHRF1 was overexpressed in the taxane-resistant cancer cells, which m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 38 publications
6
39
0
Order By: Relevance
“…Moreover, the resistance to docetaxel on invasion in the resistant cells could be partially reversed through siRNA-mediated FOXM1 inhibition. These data are consistent with the previous studies which revealed that overexpression or downregulation of FOXM1 could significantly modulate the effects of multiple chemotherapeutic drugs on cell migration and invasion [8][9][10][11][12]. These data confirm the oncogenic role of FOXM1 in the maintenance of the tumor invasion and metastasis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, the resistance to docetaxel on invasion in the resistant cells could be partially reversed through siRNA-mediated FOXM1 inhibition. These data are consistent with the previous studies which revealed that overexpression or downregulation of FOXM1 could significantly modulate the effects of multiple chemotherapeutic drugs on cell migration and invasion [8][9][10][11][12]. These data confirm the oncogenic role of FOXM1 in the maintenance of the tumor invasion and metastasis.…”
Section: Discussionsupporting
confidence: 93%
“…Recent studies have demonstrated that FOXM1 is frequently overexpressed in different kinds of cancers, including PCa, and is confirmed to be highly correlated with the proliferation and metastasis of many cancers [3][4][5][6][7]. Moreover, several studies indicated that FOXM1 overexpression conferred acquired chemotherapy tolerance through the regulation of many genes, including ATP-binding cassette genes [8][9], DNA damage repair genes [10], apoptosis-associated genes [11], cancer stem cell-related genes [12][13], and so on.…”
mentioning
confidence: 99%
“…Moreover, the docetaxel resistance of invading cells could be partially reversed through siRNA-mediated FOXM1 inhibition. These data are consistent with the previous studies which revealed that overexpression or downregulation of FOXM1 could signi cantly modulate the effects of multiple chemotherapeutic drugs on cell migration and invasion [9][10][11][12][13]. These data con rm the oncogenic role of FOXM1 in the maintenance of the tumor invasion and metastasis.…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies have demonstrated that FOXM1 is frequently overexpressed in different kinds of cancers, including PCa, and is con rmed to be highly correlated with the proliferation and metastasis of many cancers [4][5][6][7][8]. Moreover, several studies indicated that FOXM1 overexpression conferred acquired chemotherapy tolerance through the regulation of many genes, including ATP-binding cassette genes [9][10], DNA damage repair genes [11], apoptosis-associated genes [12], cancer stem cell-related genes [13][14], and so on. In our previous study, we reported that FOXM1 overexpression can signi cantly reduce the inhibitory effect of docetaxel on cell proliferation in PCa by inducing autophagy [15].…”
Section: Introductionmentioning
confidence: 99%
“…As we mentioned above, there are a number of mechanisms proposed to illuminate the development of docetaxel resistance, for instance, altered tumor microenvironment, 32 drug efflux genes, 33 cancer stem cells, 34 antiapoptotic mechanism, 35 and so on. Besides these, aberrant AR might be a critical factor in drug resistance 36 .…”
Section: Discussionmentioning
confidence: 99%